(untitled) (Journal of Scientific Research, 2015)
We have investigated Vickers hardness and the thermodynamic properties of the recently discovered nanolaminate carbide Ti3SnC2 polymorphs using the first-principles calculations. The chemical bonding shows a combination of covalent, ionic and metallic types. The strong covalent bonding is mainly responsible for high Vickers hardness of Ti3SnC2 polymorphs. Thermodynamic properties are studied using the quasi-harmonic Debye model. The variation of bulk modulus, thermal expansion coefficient, specific heats, and Debye temperature with applied pressure (P) and temperature (T) are investigated systematically within the ranges of 0 - 50 GPa and 0 - 1000 K. The calculated results have been compared with available experimental and theoretical data.